ESTUDO “IN VIVO” DA INFLUÊNCIA DO INTERVALO DE TEMPO ENTRE A APLICAÇÃO DO DENTIFRÍCIO E A ADMINISTRAÇÃO DA SOLUÇÃO DE DIGLUCONATO DE CLOREXIDINA A 0,12% NO CONTROLE QUÍMICO DO BIOFILME DENTAL E DO SANGRAMENTO GENGIVAL - Sousa, Andrea Maria de (2004)
The use of antimicrobial agents for dental biofilm formation chemical control is common after toothbrushing. Some authors have speculated a possible interaction between the clorhexidine molecule and laurel sulfate detergent present in dentifrices. The purpose of this cross-sectioned, double-blinded study was to evaluate the influence of the time interval between the usage of a dentifrice and the aministration of clorhexidine digluconate at 0.12% in vivo. The sample consisted of 20 individuals with no periodontal disease. All received during the three experimental phases the following treatment: G1 – mouthrinse with clorhexidine digluconate at 0.12% solution for 30 minutes after the removal of the dentifrice from the oral cavity; G2 - mouthrinse with clorhexidine digluconate at 0.12% solution immediately after the removal of the dentifrice from the oral cavity; G3 – mouthrinse with a placebo solution immediately after the removal of the dentifrice from the oral cavity. Scores were obtained for every subject by classifying the mechanical control of plaque formation using the Turesky Plaque Index (1970) and Gingival Inflammation Index of Mombelli (1987). Collected data was grouped and analyzed with the non-parametric Friedman test (p<0,05). Significant statistical difference between the three groups was found where group 1 presented the least overall scores followed by group 2 and 3. With the methodology used, it can be concluded that the time between the usage of dentifrice and mouthrinse with clorhexidine digluconate at 0.12% can influence the efficiency in the chemical control of the dental biofilm formation.